2014
DOI: 10.5372/1905-7415.0804.322
|View full text |Cite
|
Sign up to set email alerts
|

Rate of sentinel lymph node identification using isosulfan blue dye in breast cancer patients at Charoenkrung Pracharak Hospital, Thailand

Abstract: Background:The sentinel lymph node (SLN) is the first lymph node to receive lymphatic drainage from a primary breast tumor. If the SLN contains no metastatic tumor, then it is unlikely other lymph nodes will contain breast cancer metastasis. When the SLN does contains metastasis, an axillary lymph node dissection (ALND) is recommended to further stage the axilla and to maintain locoregional control. SLNs can be identified by using a dye, radioisotope, or combined techniques. Objective: To determine the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…A study was conducted in India by Asthurkar AV., [30] showed there was no relation between age and Tumor size. Georgette S. W., et al, [31] the greater the T stage, the higher the incidence of Level I and level II involvement (4.4% in T1 and 36.35% in T2) which is just similar to our study. In the maximum study there were no relation in between Tumor site, location and sentinel lymph node biopsy procedure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A study was conducted in India by Asthurkar AV., [30] showed there was no relation between age and Tumor size. Georgette S. W., et al, [31] the greater the T stage, the higher the incidence of Level I and level II involvement (4.4% in T1 and 36.35% in T2) which is just similar to our study. In the maximum study there were no relation in between Tumor site, location and sentinel lymph node biopsy procedure.…”
Section: Discussionsupporting
confidence: 92%
“…The ACOSOG Z0011 study showed no difference in local or regional recurrence between patients with single positive sentinel lymph nodes who were randomized or either SLNB only or SLNB and ALND. Alberitini et al, [31] showed combined dye directed and probe directed mapping in 62 patients with primary early breast carcinoma, the detection rate was higher (92%) in combined group than dye (73%) only group. The current study showed in ALND sub group, wound infection rate was 5.5% and the seroma formation in axilla was only in 3 cases (16.7%) and paresthesia in arm found in 11.1% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for failure of sentinel lymph node localization may be prior excision of the breast tumor or prior axillary node surgery or faulty techniques etc. [18]. In our study, we were not able to exactly identify the cause, but one of the reasons could be that not all the patients were administered with radiocolloid by same nuclear medicine physician which can be lead to varying results due to varying techniques.…”
Section: Discussionmentioning
confidence: 87%